THE EFFECTS OF GREEN CULTURE AND EMPLOYEE MOTIVATION ON GREEN WORKPLACE PRACTICE IN THE FOOD AND BEVERAGE INDUSTRY IN INDONESIA - Rosyanti, Daisy Marthina; Khoirotunnisa, Fani; Dewanti, Mentari Clara (Universitas Brawijaya, Indonesia, 2023)
The issue of green business practices has become an exciting topic to study in recent years. To achieve the SDGs, applying Green Human Resources Management in green business practices is an essential aspect because of its role as a key factor in the company's success. Given that the Food and Beverage industry is one of the industries with the most millennial generation employees, the support for millennial teamwork on green business practices is urgent in this study,